Riwayat Hafs B. Sulayman Al-Kufi: kajian perbandingan antara Tariq al-Syatibiyyah dengan al-Jazariyyah = رواية حفص بن سليمان الكوفي - Abd. Hamid, Felza Zulhibri (Sohabah Salam entreprise, 2017)
This study is to compare Tariq al-Shatibiyyah and al-Jazariyyah in the riwayah of Hafs b. Sulayman al-Kufi. This riwayah has been practiced by ninety five percent of muslims in the world including Malaysia. This topic is chosen for studies because there has been much confusion arising in the muslim society especially in Malaysia with regards to the identity of the riwayah. Studies show that it is crucial to explain the terms first so as the objective of this study is not sidelined. Other than introducing briefly the background of Imam Hafs b. Sulayman al-Kufi, the scope of the riwayah is also being touched adequately from the fifty two turuq that has been recognized as mutawatirah by Islamic scholars as written in the book of al-Nashr by Ibn al-Jazari. Besides, this study also explains the difference in the riwayah of Hafs b. Sulayman al-Kufi by comparing the two tariq namely al-Shatibiyyah and al-Jazariyyah. The difference is explored from the point of theoretical understanding and its implications in the orthography of the masahif. In addition, this also shows that the knowledge of correct theoretical understanding in tajwid must be hand in hand with understanding of al-Qira’at. This is because there are some arguments on the subject of tajwid that involve a substantial knowledge of the al-Qira’at. Thus, this library research based, utilizes various methods which are comparative, historical, documentational and observational as the means for data collection and analysis. Therefore, the outcome had shown that there was confusion among the Muslim society in Malaysia with regard to the identity of riwayah Hafs b. Sulayman al-Kufi. This confusion, if not rectified with a comprehensive explanation will probably cause a problem in understanding the riwayah Hafs b. Sulayman al-Kufi in terms of comprehension and the al-Qur’an’s mutawatirah recitation as a whole.